Physico-mechanical properties of Paraserianthes falcataria (Batai) in relation to age and position variation - Roslan, Sarah-Nur Hanis; Salim, Sabiha; Muhammad Roseley, Adlin Sabrina; Zainal Abidin, Wan Nur Shasha Najiha (Universiti Putra Malaysia Press, 2024)
Paraserianthes falcataria, locally known as Batai, is a non-native, fast-growing species selected by Malaysia’s forest plantation programme. Limited empirical studies have been conducted regarding this species, specifically the one planted domestically. A comprehensive understanding of its wood properties is essential to effectively introduce and utilise this species commercially. Thus, a study was conducted to evaluate the physico-mechanical properties of Batai and their correlation with age and position variation. In this study, P. falcataria was harvested from a forest plantation in Kuala Krai, Kelantan, Malaysia, encompassing three different age variations: 2.5, 5 and 8 years. Five replicates were felled for each age, and the logs were segmented into three 2 m portions representing variations along the vertical axis: top, middle and bottom. Additionally, radial variation was examined by distinguishing between heartwood and sapwood. Subsequently, samples were tested with static bending and compression tests following standard protocols (ISO 13061-3: 2014, ISO 13061-4, and ISO 13061-17: 2017). The results revealed statistically significant physico-mechanical properties among different ages and within-tree sections. This study provides valuable documentation on P. falcataria wood properties, contributing to the field’s knowledge. Moreover, it exposes the harvesting determinants towards the planters and wood industry, facilitating better utilisation of P. falcataria wood across various applications.